Language learning methods and techniques for children with special needs (Training and Practice : Journal of Educational Sciences, 2019)
We can read about the problem in several forums and it is one of the most researched neural disorders. In June 2018, the WHO Diagnosis Classification System displayed ICD-11 (The International Statistical Classification of Diseases and Related Health Problems) as a learning disorder that includes reading, writing and counting difficulties. We are not talking about the disorder of intellectual development, but rather as a result of the disruption of perception, movement and sensory integration. This can also occur as a result of genetic but environmentalinduced developmental disorders. In this paper, we will review the difficulties of reading, writing and counting which causes the difficulties of performance and how it occurs in children when learning a foreign language, and how we can help them with the process.